Predictive value of longitudinal changes of serum matrix metalloproteinase-9 and brain-derived neurotrophic factor in acute ischemic stroke - Li, Youjia; Han, Xiaoyan; Luo, Songbao; Huang, Huiqin; Huang, Xinyan; Li, Miaochang; Huang, Yan; Chen, Ying; Wu, Zhenmei (Frontiers in Aging Neuroscience, 2022)
Background: Matrix metalloproteinase 9(MMP-9) and brain-derived neurotrophic factor (BDNF) have documented roles in the inflammatory injury cascade of neurovascular units following ischemic brain injury. However, their dynamic changes and predictive values after acute ischemic stroke (AIS) have not been well elucidated. Objective: To investigate the temporal profiles of serum MMP-9 and BDNF concentrations and their relationship with the prognosis in patients with AIS. Methods: MMP-9 and BDNF levels were measured in 42 AIS patients in prospectively collected blood samples, which were taken on the first day (T1), the second day (T2), and the fifth day (T5) after admission. Healthy subjects (n=40) were used as controls. The AIS patients were divided into groups of good functional prognosis (n = 24) and poor prognosis (n = 18) according to their modified Rankin Scale score at 3 months. Longitudinal analysis of MMP-9 and BDNF and their association with neurological prognosis was performed using repeated measurement ANOVA. Results: At baseline(T1), the level of serum MMP-9 and BDNF were significantly higher in AIS group than in the normal control group (P < 0.01). Repeated measurement ANOVA showed a significant main effect and interaction of MMP-9 between good prognosis and poor group (P < 0.05). Further simple-effect analysis showed that the MMP-9 level was significantly increased in the poor prognosis group compared with the good prognosis group at T5 (P < 0.05). There were the significant time-dependent and the interaction effect (all P < 0.05), but no main effect (P > 0.05) for BDNF. Compared with the poor prognosis group, the simple-effect results indicated that the BDNF level of the good prognosis group was lower at T1, while the same was reversed for expression at the T5 (P<0.05). Conclusions: MMP-9 and BDNF are closely related to the prognosis of patients with AIS in a time-dependent manner. The dynamic changes of the two biomarkers are superior to baseline levels in predicting the prognosis of AIS patients. A sustained decrease in MMP-9 and increase in BDNF levels in AIS patients after several days of treatment implied a favorable prognosis.